Investigation the Understanding of Mazandaran’s Rice Farmers About the Climate Change and their Approaches to Tackle it - ANAHITA Kheirkhah; Gholam Ali Kamalii; Amir Hussain Meshkatee; Hossein Babazadeh; Ebrahim Asadi Oskouei (Nīvār)
Identifying the local people's attitude towards climate change and the traditional and modern solutions they took to adapt can be very useful in managing the effects of climate change. The purpose of this research is to present the views and attitudes of the native rice farmers of Mazandaran with climate change and adaptation strategies to it. In order to do this, first, the opinions of the local people about climate change and the strategies to adapt to it were measured using a questionnaire method, and they were processed using statistical methods. After determining the adaptation strategies index (ASI), 19 presented strategies were ranked so that the results can be used for more effective policies to adapt to climate change and provide better services to the local rice farmers of Mazandaran. The results showed that more than 50% of the rice farmers in the region have felt and experienced climate change and its effects, and the most important consequences of climate change in the rice sector are the reduction of soil fertility, the use of more fertilizer and the increase of pests and diseases, early planting and This is followed by the damage of the late spring cold, the increase in the time the seedlings stay in the treasury and the decrease in drinking and agricultural water, and solutions such as public fight against pests, provision of subsidized fertilizers and poisons, management of irrigation time and sustainable water management are the solutions selected by local people .